Solid Waste Management: Between Legislation and Practical Implementation (Libyan Journal of Ecological & Environmental Sciences and Technology, 2026)
If the environment is understood as the natural setting in which human beings and other living organisms live, it simultaneously represents a challenge that humanity must confront. This challenge is embodied in the problem of environmental pollution, which has placed humanity before a real and imminent threat to its food, water, air, health, agriculture, forests, and civilization. Pollution has corrupted, harmed, and endangered every aspect of life. Consequently, it became imperative for the international community to convene conferences, examine this issue thoroughly, and adopt the decisions and measures necessary to preserve the environment and protect human beings and all living organisms. Among the most significant outcomes of these efforts was the establishment of a legislative framework for dealing with solid waste in order to ensure a safe and healthy environment for humanity.One of the main reasons that motivated me to undertake this study is the phenomenon of waste accumulation, which has also drawn the attention of many specialists in the field of environmental studies. This interest increased especially after reviewing numerous scientific studies and accurate ecological statistics that revealed the scale of the damage resulting from the accumulation of waste, as well as the magnitude of the risks it poses to the present generation and future generations alike. This issue deeply alarmed me and led me to believe that we are, indeed, moving rapidly toward serious environmental deterioration. Accordingly, I considered it my duty, first as a citizen living in this country, and second as an academic legal scholar, to contribute, within my area of specialization, to the defense of the environment, particularly against the dangers of pollution. This includes raising public awareness about the seriousness of this phenomenon, emphasizing the need to put an end to such indifference, and analyzing the challenges that hinder the effective implementation of environmental rights and limit their practical realization.The problem of this study lies in the worsening phenomenon of waste accumulation, the lack of serious and effective measures to address it, and the ambiguity and duplication found in the legislative texts relating to environmental protection from pollution in Libya. It is also reflected in the overlap and inconsistency of administrative procedures in terms of jurisdiction and compliance. Accordingly, the central question raised by this study is: To what extent is the claim valid that the existing legislative framework constitutes an obstacle to improving public services? Furthermore, what is the fate of the human right to live in a clean and healthy environment?
Keywords: Solid waste management; Environmental law; Governance; Sustainability; Libya